Examination of overhead and single-leg squat kinematics and lower extremity injury in female collegiate athletes - Lisman, P. J.; Wilder, J. N.; Hansberger, B. L.; Zabriskie, H. A. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Overhead squat (OHS) and single-leg squat (SLS) tests have been used as screening tools to identify injury risk in athletic populations. Yet, no study has examined the association between specific trunk and lower extremity (LE) kinematic measures acquired during OHS and SLS performance and LE injury incidence in female collegiate athletes. The purpose of this study was to examine the association between LE and trunk kinematics captured during OHS and SLS performance and LE injury in female collegiate athletes. METHODS: This was a prospective cohort study. One hundred eight Division I female collegiate athletes underwent OHS and SLS testing before the start of their competitive season. A Microsoft Kinect sensor using Athletic Movement Assessment software (PhysiMax®) was used to capture kinematic variables: hip flexion, knee flexion, knee frontal plane projection angle (FPPA), and trunk flexion. Participants were tracked during one competitive season for incidence of LE injury. Logistic regression models were used to examine the association between OHS and SLS measures and injury. RESULTS: Twenty-three (21.3%) participants suffered a LE injury. No significant associations were found between any OHS (odds ratio [OR] range: 0.91-1.08) or SLS (OR range: 0.81-1.22) kinematic measure and incidence of LE injury. CONCLUSIONS: Sagittal plane LE and trunk kinematics and knee FPPA during OHS and SLS performance were not associated with LE injury in this cohort of athletes. Our findings do not support the use of these select kinematic measures captured during OHS and SLS testing as stand-alone injury risk assessments in female collegiate athletes.